Controlled drug release from antibiotic‐loaded layered double hydroxide coatings on porous titanium implants in a mouse model. Issue 6 (31st October 2014) - Badar, Muhammad; Rahim, Muhammad Imran; Kieke, Marc; Ebel, Thomas; Rohde, Manfred; Hauser, Hansjörg; Behrens, Peter; Mueller, Peter P.
Abstract As an alternative to degradable organic coatings the possibility of using layered double hydroxides (LDHs) to generate implant coatings for controlled drug delivery was evaluated in vivo and in vitro. Coatings prepared from LDH suspensions dissolved slowly and appeared compatible with cultured cells. LDH coatings loaded with an antibiotic resulted in antibacterial effects in vitro. The LDH coating prolonged the drug release period and improved the proliferation of adherent cells in comparison to pure drug coatings. However, during incubation in physiological solutions the LDH coatings became brittle and pieces occasionally detached from the surface. For stress protection porous titanium implants were investigated as a substrate for the coatings. The pores prevented premature detachment of the coatings. To evaluate the coated porous implants in vivo a mouse model was established. To monitor bacterial infection of implants noninvasive in vivo imaging was used to monitor luminescently labeled Pseudomonas aeruginosa. In this model porous implants with antibiotic‐loaded LDH coatings could antagonize bacterial infections for over 1 week. The findings provide evidence that delayed drug delivery from LDH coatings could be feasible in combination with structured implant surfaces. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 2141–2149, 2015.